The Relationship Between Self Esteem And Facebook Addiction In Adolescents In Kupang City - Joanina Adriana Seran; M. Dinah Charlota Lerik; R. Pasifikus Christa Wijaya; Apris A Adu (Journal of Health and Behavioral Science, 2020)
Abstract: This research is quantitative research, with the method used is correlational. The sampling technique uses Convenience Sampling with a total sample of 409 subjects. Subjects in this study were teenagers who played Facebook in the past year with an age range of 13-22 years. Data analysis using Sperman Rank test. The results of Sperman's correlation between Facebook addiction and self-esteem point to -.0.242 with a significance value of 0,000. the significance value obtained is 0,000 <- 0,242, then there is a significant relationship between the research variables. Because the correlation coefficient number is negative, the correlation is inversely proportional. The higher Facebook addiction the lower self-esteem of teenagers in Kupang or the Lower Facebook Addiction the higher self-esteem in adolescents in the city of Kupang.Keywords: Self-Esteem, Facebook, Facebook Addiction, Teenagers